A comparison of operational risk in banks of United Kingdom and China - JIANG, KAITIAN (2014)
This dissertation mainly compares the operational risk in banks of the United Kingdom (UK hereafter) and China by measuring the operational risk and estimating the firm-specific and macroeconomic determinants of operational risk in both the UK and China separately. Four main findings are concluded from the comparison of operational risk in banks of the UK and China. It suggests that larger banks with better profitability, less solvency risk, less growth opportunity, better efficiency and greater numbers of employees would prepare more capital to operational risk in banks of the UK. By contrast, in China, a larger sized bank with a better liquidity position and more staff settings would require more capital for operational risk in China. It also implies that banks in the UK are more likely to be affected by the status of internal control management. In addition, operational risk in Chinese banks is more significantly affected by the number of employees when compared with UK banks. Additionally, the more significant relationship between regulatory capital of operational risk and the liquidity in Chinese banks suggests that the operational risk management might be able to be improved by enhancing the liquidity management in Chinese banks. With regard to the macroeconomic factors, as well as the final findings, this indicates that operational risk in Chinese banks is more likely to be impacted by macroeconomic factors than in UK banks. These findings highlight the differences between operational risk in UK banks and Chinese banks, as well as the role of each determinant played in improving operational risk in banks of each country.